SISTEM PAKAR TIPE PERUMAHAN MENGGUNAKAN METODE FORWARD CHAINING - ona maliki; Fandi Dangkua (Universitas PGRI Semarang, 2018)
Several house constructions do not often follow certain old patterns in its creation. Additionally, the owners have their willingness and dream in the houses that would be classified into various types of building by an architect. This condition raised a problem in which it complicated the owners to have a preliminary consultation with architect regarding recommendation of type and house specification based on budget and land area. In Gorontalo, architect services are mostly used to build a house in a housing area, particularly those who are in the middle to the upper level. In some cases, the owner should come consulting with the architect directly. The research aimed to apply forward chaining method as a recommendation of residence type for the owner. The system development method applied waterfall method. The research finding was Expert System of Housing Type through an application of forward chaining method functioned by using PHP programming language and MySQL storage as well as the application that is equipped by knowledge as experts’ that can recommend the appropriate type and specification design based on willingness and necessity of owner. The aspect of house type determination is based on land size where the house to be constructed and aspect of house specification determination is seen from material selection and use